2020
DOI: 10.1007/s40962-020-00412-7
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Silicon Microsegregation in Solid-Solution-Strengthened Ductile Iron by Alloying with Aluminum

Abstract: In solid-solution-strengthened ferritic ductile iron (SSFDI), a silicon content above 4.3 wt% leads to an abrupt decrease in ultimate tensile strength and elongation at fracture. This phenomenon has recently been proven to be attributed to the formation of iron-silicon long-range orderings that lead to an embrittlement of the material. It is assumed that the local tendency to form silicon superstructures is promoted in particular by the occurrence of silicon microsegregation. During solidification of ductile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A new DI classification called High-Silicon Ductile Iron (HSDI) has recently been introduced for DI with Si content ranging from 3.2 to 4.3 wt.%. It has been reported that with increasing Si content, hardness, tensile strength, and yield strength properties are promoted, while elongation to failure decreases [8,[12][13][14] and machinability and corrosion resistance improve [15][16][17][18]. These results suggest a potential advantage in the production process and performance over DI with lower Si content [10,11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A new DI classification called High-Silicon Ductile Iron (HSDI) has recently been introduced for DI with Si content ranging from 3.2 to 4.3 wt.%. It has been reported that with increasing Si content, hardness, tensile strength, and yield strength properties are promoted, while elongation to failure decreases [8,[12][13][14] and machinability and corrosion resistance improve [15][16][17][18]. These results suggest a potential advantage in the production process and performance over DI with lower Si content [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…In terms of mechanical properties, Si has a significant effect on the toughness and tensile strength of ferritic DI. As the Si content increases, the yield strength and tensile strength also increase [8][9][10][11]. A new DI classification called High-Silicon Ductile Iron (HSDI) has recently been introduced for DI with Si content ranging from 3.2 to 4.3 wt.%.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be understood based on the principles of metal physics. Silicon atoms segregate during the solidification of Si-DCI [ 9 ]. Since the diffusion time is too short to homogenize the segregation profile, high Si contents remain in the vicinity of the graphite and decrease towards the interstices of the graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Promising approaches exist to manipulate the segregation profile, as indicated by Franzen et al [ 9 ], and thereby tailoring the mechanical properties of Si-DCI. However, only little in-depth experimental studies of the influence of the Si-segregation profile on the mechanical properties of Si-DCI were published in the literature [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that combining high ductility with high strength values is essential to produce dynamically loaded parts. Such premise intrigued many researchers to study the effect of small additions of niobium on different types of cast iron alloys [12][13][14][15][16][17][18][19][20][21][22][23][24]. The effect of Nb alloying differs to some extent according to the type of cast irons.…”
Section: Introductionmentioning
confidence: 99%